Endoscopic features and clinical outcomes of cytomegalovirus gastroenterocolitis in immunocompetent patients - Jiyoung Yoon (Nature Portfolio, 2021)
Abstract We aimed to investigate the endoscopic features and clinical course of CMV gastroenterocolitis in immunocompetent patients. We reviewed the medical records and endoscopic images of 86 immunocompetent patients with CMV gastroenterocolitis. Immunocompetent patients were defined as those without congenital or acquired immunodeficiency syndrome, use of anti-cancer chemotherapeutic and immunosuppressive agents, and inflammatory bowel diseases. The mean age was 65.5 ± 11.8 years and 53 (61.6%) were male. Sixty-eight (79.1%) patients had comorbidities. Upper gastrointestinal-dominant, small bowel-dominant, and colon-dominant types were observed in 19, 7, and 60 patients, respectively. Endoscopic features could be classified into discrete ulcerative type with/without exudate and diffuse erythematous type with/without exudate. Antiviral treatment with ganciclovir was initiated in 51 patients (59.3%), 40 of whom improved and 1 improved after changing ganciclovir to foscarnet. Thirty-three patients (38.4%) improved without antiviral treatment. Surgery was necessary in two patients because of colon perforation before antiviral treatment. Another two patients underwent surgery because of sigmoid stricture and cecal perforation during antiviral treatment. Endoscopic type was not associated with clinical outcomes, such as surgery and death. CMV gastroenterocolitis in immunocompetent patients mostly occur in older patients with comorbidities, and the endoscopic features vary with no association with clinical outcomes.